Uncertainty, Threat, and International Security Implications for Southeast Asia - Savic, Ivan (Rethinking Asia and International Relations, 2017)
The rise of China is changing the strategic landscape globally and regionally. How states respond to potential threats posed by this new power arrangement will be crucial to international relations for the coming decades. This book builds on existing realist and rationalist concepts of balancing, bandwagoning, commitment problems, and asymmetric information to craft explanations about how states respond when faced with potential threats. Specifically, the book explores the role different types of uncertainty play in potential balancing situations. Particular focus is given to the nature of the rising state's actions, the balance of forces, and the value of delay. These concepts are analysed and illustrated through a series of case studies on Europe in the 1930s as well as the present-day Southeast Asia, looking at great powers such as Britain and France, but also a wide range of smaller powers including Poland, Yugoslavia, Vietnam, and the Philippines.